Measured transfer length of 15.2-mm (0.6-in.) duplex high-strength stainless steel strands in pretensioned girders. (15th June 2021) - Al-Kaimakchi, Anwer; Rambo-Roddenberry, Michelle
Highlights: Transfer length of 15.2-mm- (0.6-in.-) diameter stainless steel strand was evaluated. Strand release sequence among multiple girders' ends affects transfer lengths. Type of confinement reinforcement had no significant effect on transfer length. AASHTO and Eurocode 2 conservatively predicted transfer length of HSSS strands. Abstract: Duplex High-Strength Stainless Steel (HSSS) corrosion-resistant strands are desirable in concrete members in extremely aggressive environments to mitigate corrosion problems. Recently, HSSS strand was introduced to the construction industry in 15.2-mm- (0.6-in.-) diameter size. To practically use the 15.2-mm- (0.6-in.-) diameter HSSS strand in pretensioned concrete members, its transfer length needs to be evaluated using full-scale members, and the applicability of the prediction models in design provisions requires examination. A total of eight 12.8-m- (42-ft-) long AASHTO Type II girders were fabricated using the long-line method. Five girders were prestressed with HSSS strands while the other three were prestressed with carbon steel strands. The initial prestressing stress was 1102 MPa (159.8 ksi) for HSSS strand and 1396 MPa (202.5 ksi) for carbon steel strand. Three different types of confinement reinforcement were used: carbon steel, glass fiber reinforced polymer (GFRP) and duplex stainless steel. The effects of type and spacing of confinement reinforcement on transfer length were evaluated. The effect of the strand release sequence among multiple girders' ends in the casting bed on transfer length was investigated. Predictive models from all evaluated design provisions were conservative, with different accuracy, in estimating the transfer lengths of HSSS and carbon steel strands. Eurocode 2 was relatively the most accurate provision among the evaluated design provisions, while AASHTO LRFD, which had the simplest equation (60 db ), was the most conservative provision. Because HSSS strands are relatively new, there are no design guidelines available for their use in pretensioned concrete members. Therefore, findings from this experimental study will be helpful in the development of design guidelines.